ANALISIS PENGAMBILAN KEPUTUSAN ADOPSI STAKEHOLDER DALAM PEMBUATAN PROVINCIAL HEALTH ACCOUNT (PHA) DI PROVINSI JAWA TENGAH - Cindi Widia Lestari; Sutopo Patria Jati; Antono Suryoputro (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Abstract: One of the attempts in perform the function of financing in the Health System through Health Account. Health Account is a respresentative and innovative resources to describe the utilization of the flow of funds/ financing used for planning appropriate health budgets to solving health problems. In the implementation of drafting the Provincial Health Account in Central Java was still find problems. They are the absence of formal team, result of PHA have not been disseminated, the difficulty of collecting data, and the difficulty of presenting relevant stakeholders. The purpose of this study was to analyze the decision-making adoption of stakeholders in the making PHA in Central Java province. The variables of this study is Knowledge Stage, Persuassion Stage, and Adoption Decision Stage. The study used a qualitative method with descriptive approach and interview guide was used as an instrument. Interviews were conducted with Health Department of Central Java, Planning and Regional Development Agencies of Central Jawa, Central Bureau of Statistics, Tugurejo Hospital, and Ministry of Health. The findings indicate that Knowledge Stage of stakeholders is good because all stakeholders have to known the concept and elements of the PHA. Persuasion Stage of stakeholders has been good enough for stakeholders expressed the making PHA has a relative advantage, compatibility with regional health system, can be made by Central Java, and can be seen the results even though the making PHA is considered quite difficult to do. Adoption Decision stage, all stakeholders declared accept innovation of the making PHA because it has advantages and stakeholders have made various preparations for the making PHA. Based on that all stages sufficient to support the decision to accept innovation of the making PHA.